Cell surface Nucleolin represents a novel cellular target for neuroblastoma therapy - Brignole, Chiara (2021)
Neuroblastoma (NB) represents the most frequent and aggressive form of extracranial solid tumor of infants. Nucleolin (NCL) is a protein overexpressed and partially localized on the cell surface of tumor cells of adult cancers. Little is known about NCL and pediatric tumors and nothing is reported about cell surface NCL and NB. Methods: NB cell lines, Schwannian stroma-poor NB tumors and bone marrow (BM)-infiltrating NB cells were evaluated for the expression of cell surface NCL by Flow Cytometry, Imaging Flow Cytometry and Immunohistochemistry analyses. The cytotoxic activity of doxorubicin (DXR)-loaded nanocarriers decorated with the NCL-recognizing F3 peptide (T-DXR) was evaluated in terms of inhibition of NB cell proliferation and induction of cell death in vitro, whereas metastatic and orthotopic animal models of NB were used to examine their in vivo antitumor potential. Results: NB cell lines, NB tumor cells (including patient-derived and Patient-Derived Xenografts-PDX) and 70% of BM-infiltrating NB cells show cell surface NCL expression. NCL staining was evident on both tumor and endothelial tumor cells in NB xenografts. F3 peptide-targeted nanoparticles, co-localizing with cell surface NCL, strongly associates with NB cells showing selective tumor cell internalization. T-DXR result significantly more effective, in terms of inhibition of cell proliferation and reduction of cell viability in vitro, and in terms of delay of tumor growth in all NB animal model tested, when compared to both control mice and those treated with the untargeted formulation. Conclusions: Our findings demonstrate that NCL could represent an innovative therapeutic cellular target for NB.